The means-end chain in consumer decision making: the case of Porsche - Kahle, Lynn R. (Henry Stewart Talks, 2019)
This case study uses the Porsche brand to explore the importance of the means-end chain in consumer decision making. As the example demonstrates, reasons for purchase are often determined by our core values – the end point of the means-end chain.